PENGARUH GAYA KEPEMIMPINAN TERHADAP PRESTASI KERJA PEGAWAI BADAN LINGKUNGAN HIDUP KABUPATEN KUTAI TIMUR - Mardiana, Maratus Sholikhah, H.Eddy Soegiarto,K , (EKONOMIA, 2015)
This study aims to determine the influence of leadership style on job performance of employees Environmental Agency of East Kutai. This study is a scientific information regarding the assessment of leadership styles and their indicators, employee performance assessment methods, and the relationship between leadership style with employee job performance Environmental Agency of East Kutai. Application of appropriate leadership style to the work environment will encourage an increase in work performance of employees, will thus have a positive impact for the organization. Hypothesis testing is done by spreading the questionnaire 50 Employee Environmental Agency of East Kutai.By using simple linear regression analysis, it can be concluded that leadership style variable (X) a significant effect on Employee Job Performance (Y).